4x+32-4=34-2x

Simple and best practice solution for 4x+32-4=34-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+32-4=34-2x equation:


Simplifying
4x + 32 + -4 = 34 + -2x

Reorder the terms:
32 + -4 + 4x = 34 + -2x

Combine like terms: 32 + -4 = 28
28 + 4x = 34 + -2x

Solving
28 + 4x = 34 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
28 + 4x + 2x = 34 + -2x + 2x

Combine like terms: 4x + 2x = 6x
28 + 6x = 34 + -2x + 2x

Combine like terms: -2x + 2x = 0
28 + 6x = 34 + 0
28 + 6x = 34

Add '-28' to each side of the equation.
28 + -28 + 6x = 34 + -28

Combine like terms: 28 + -28 = 0
0 + 6x = 34 + -28
6x = 34 + -28

Combine like terms: 34 + -28 = 6
6x = 6

Divide each side by '6'.
x = 1

Simplifying
x = 1

See similar equations:

| .667=.333+2x | | 5x^2-2x-6=f(x) | | 6d+8=10d-12 | | f(a)=a^2+10a+21 | | (-2x+1)+(2x+10)= | | 5.3x+5.4d-8.9x+5.3d= | | (8x^2-3x-5)-(5x^2+2)=3x^2+10 | | (5x+4)+(-9x+5)= | | 4c-4=20 | | 44x+4y=20 | | f(3)=12x+14 | | 5z+3=4z+4 | | 15s-20=5s | | (-x+3)+(-9x+6)= | | 3(4c+5)=-12 | | (12r+9)(5r-15)=0 | | 16=6d+1 | | 4x+-8+2x=40 | | (7x+5)+(x+2)= | | (5-u)(2u-9)=0 | | 10-.66x=12 | | (-7x+2)+(x+4)= | | 3x-5=4x+5 | | 2(3n-3)=36 | | (x+6)+(-2x-4)= | | -3a=142 | | 11x+14-3x=2x-3 | | 7x+8=6x+20 | | f(7)=9x-23 | | x^2-9+x-30= | | 2x+6-6=15-6 | | 3(2n+2)=0 |

Equations solver categories